Lourenzo Fernández-Prieto, Juan Pan-Montojo, y Miguel Cabo (eds.), Agriculture in the Age of Fascism. Authoritarian Technocracy and Rural Modernization, 1922-1945, Turnhout, Brepols Publisher, 2014, 261 páginas - Alares López, Gustavo (Hispania Nova. Primera Revista de Historia Contemporánea on-line en castellano. Segunda Época, 2016)
--